Evaluation of antioxidant capacity of endemic plant Marrubium astracanicum subsp. macrodon: Identification of its phenolic contents by using HPLC-MS/MS - Bursal, Ercan; Aras A.; Kılıç Ö. (Taylor and Francis Ltd., 2018)
Antioxidant properties of Marrubium astracanicum subsp. macrodon solvent extracts were measured by both cupric ion reducing antioxidant capacity (CUPRAC) and ferric reducing antioxidant power (FRAP) methods. According to the results, ethanol extract of the plant has high potential of reducing antioxidant activity on CUPRAC method. However, water extract of the plant has lower antioxidant potential. Furthermore, both water and ethanol extracts showed lower reducing antioxidant activity compare to standards on FRAP method. Moreover, the composition and content of plant leaves were detected by UHPLC-ESI-MS/MS. High concentrations of quinic acid, p-coumaric acid and malic acid were determined. © 2018 Informa UK Limited, trading as Taylor & Francis Group
PubMed ID: 29842794
Keywords: Antioxidant; LC-MS/MS; Marrubium; phenolic compound